Development of Low Cost Tubular Type Indigenous Solar Cooker - Sethi, V. P; Singh, Rupinder Pal; K, Sumathy (Journal of Agricultural Engineering, 2013)
A low cost tubular type indigenous solar cooker was developed using an inflated rubber tube of a motorbike. The concept is that the compressed air in vulcanised rubber tube not only provides a thermal barrier to heat transfer and< acts as an insulator to minimize side loss,but also provides a proper self-sealing characteristic at the bottom and the top with trapped hot air not to escape. The inflated tube was placed on the upper layer of an insulating material. The inner rim area of the inflated tube functioned as cooking chamber. Absorber plate was made by cutting circular galvanized iron sheet (painted black) and placed inside the hollow tube rim area. A single glass cover of 5mm thickness was then placed over it to generate greenhouse effect inside the cooking chamber. To increase the solar flux on to the cooker, a reflector mirror was also used. Experiments were performed during the months of January and April 2012, and its performance was compared with the commercially available box type solar cooker. First (F1) and second figures of merit (F2), cooking power were compared. It was observed that the performance of tubular cooker was almost at par with the box type solar cooker. Low cost and locally available materials for constructing this cooker at home may provide benefit to the rural population for preparing one meal during the day at almost no cost.